Oral and oropharyngeal squamous cell carcinoma in young adults: A retrospective study in Granada University Hospital - Cariati, Paolo (Med Oral Patol Oral Cir Bucal, 2017)
BACKGROUND: This study aims to evaluate and analyze the clinical features and outcomes of oral and oropharyngeal squamous cell carcinoma (SCC) in patients < 45-years old in our center. MATERIAL AND METHODS: A retrospective analysis was conducted using the records of patients diagnosed with oral and oropharyngeal SCC between 1998 and 2011 in the University Hospital of Granada (Spain). The analysis identified 33 patients with oral and oropharyngeal SCC with an age of <45 years. Moreover, during the years studied, a further 472 patients were diagnosed with oral and oropharyngeal SCC in our center. Thus, 100 SCC patients with an age of >45 years were randomly selected from the same database. A retrospective analysis was conducted to determine specific features including sites of occurrence, risk factors, sex distribution, socio-economic status, T stage at diagnosis, nodal involvement, degree of tumor differentiation, locoregional failure and overall survival at 5 years was. Further, the results of both groups were compared. RESULTS: The male-female ratio was 1.2:1 in the group of young adults and 2.03:1 in the group of patients with an age of >45 years. No significant differences were found in terms of site, nodal involvement, locoregional failure, and overall survival. However, there were statistically significant differences between the two groups in terms of features such as risk factors, socio-economic status, T stage at diagnosis, and degree of tumor differentiation. The overall 5-year survival rate was 62% for patients >45 years old, whilst for the group of young adults this rate was 48.4% (p= 0.17). CONCLUSIONS: The poor association between the common risk factors and oral and oropharyngeal cancers in young adults suggests that other pathogenic mechanisms should be investigated. For young patients, the data show evidence of poorer outcomes in terms of overall survival (p=0.17), and locoregional failure (p=0.23). Nevertheless, the literature shows that the results in this field are particularly inconsistent, and further research is therefore needed to provide more in-depth knowledge of the disease in this age group. Key words:Oral and oropharyngeal squamous cell carcinoma, young adults, poor prognosis,risk factors.